Synthesis of chlorinated fullerenes C60Cln (n = 2, 4) from C60Cl6 and their Arbuzov-type reaction with P(OEt)3. Issue 7 (14th February 2018) - Zhilenkov, Alexander V.; Peregudov, Alexander S.; Chernyak, Alexander V.; Martynenko, Vyacheslav M.; Troshin, Pavel A.
Graphical abstract: Highlights: Reduction of C60 Cl6 with PPh3 produces the lowest chlorinated fullerenes C60 Cln (n = 2–4) Chlorofullerene 1, 4-C60 Cl2 was isolated and characterized for the first time. A mixture of C60 Cl2-4 was successfully used for the preparation of C60 [P(O)(OR)2 ]3 H. Abstract: Reduction of C60 Cl6 with triphenylphosphine was demonstrated to be a useful method for the preparation of a mixture of low-chlorinated fullerenes C60 Cln (n = 2, 4). Individual chlorofullerene 1, 4-C60 Cl2 was isolated by preparative gel permeation chromatography and characterized spectroscopically for the first time. The Arbuzov-type reaction of C60 Cln with P(OEt)3 produced C60 [PO(OEt)2 ]3 H as a major isolable product, which was further hydrolyzed to C60 [PO(OH)2 ]3 H.